(3Jbhje GdPgf aj GdefWbs - (3CejI Hf YHO GdYRjR GdCfOdSj, CHh GdUdJ,J (B529 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg JYGdi Mb MeOg hGdUdGI Ydi eMeO hYdi Bdg GdCHQGQ GdaUd GdChd ai GdeYGfi GdcdjI GdNeSjI GdZQV GdCTQa HGdbhGfjf GdefWbjI MUhd GdYde s
(3BNQgG (B:s
(3hCaVd GdWQb GdeDOjI Edi GdMOhO gi WQjb GdJQcjH GdJi gi WQjb CQSWhWGdjS ced GdeNJUQ HeYhfI GdhGgH ddYhf hGdMeO ddg ceG gh Cgdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B469s
(3eUOQ GbJfGA GdCUd (B:s
(3eOQjO (B(646/1) s
Keywords: (3GdadSaI hGdefWbs